KOHESI GRAMATIKAL DALAM NOVEL SI PARASIT LAJANG KARYA AYU UTAMI (KAJIAN WACANA) - Dwi Septiani; Maharani Mutiara Rahmah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
Abstract This learn about examines grammatical cohesion in novel of Si Parasit Lajang by Ayu Utami entitled. The motive of this lookup is to explain the use of grammatical concord in Ayu Utami's novel, titled Si Parasit Lajang. The results of grammatical cohesion contained in the sentences in the novel Si Parasit Lajang in the form of substitution (recovery), reference (referencing), ellipsis (impulse), and conjunction (connecting). Grammatical concord contained in sentences is used to connect entire sentences so that they turn out to be cohesive and effective. In the Ayu Utami novel entitled Si Parasit Lajang, the use of grammatical brotherly love was obtained from the most records to the least data, specifically first, the use of 896 facts conjunctions, more often than not 391 records subordinative conjunctions; second, the use of 415 references, specifically endophore references with 180 data; third, the use of ellipses as an awful lot as four data; and fourth, the use of substitution of 2 facts which solely exists in the verb substitution. Overall data as many as 1,137 data.